Pergeseran dari Offshoring ke Friend-Shoring: Penataan Ulang Strategis Rantai Nilai Global dalam Menghadapi Fragmentasi Geopolitik Dunia - Aldi Adi Pratama (Strategi : Jurnal Manajemen, 2025)
The world is currently witnessing a fundamental transformation in the global economic architecture, marked by a shift from the paradigm of offshoring driven by extreme cost efficiency toward "friend-shoring," which prioritizes national resilience and security. This study aims to analyze the impact of geopolitical fragmentation on Global Value Chains (GVCs) and how countries like Indonesia navigate these strategic shifts. Employing a mixed-methods approach, this research combines qualitative analysis through a literature review with quantitative methods, including a general equilibrium framework, Dynamic Factor Model (DFM), and Structural Vector Autoregressions (SVAR) to simulate the impact of trade cost variations on aggregate output. The findings indicate that while friend-shoring may mitigate the risks of economic coercion, such policies carry significant consequences, including a potential decline in global GDP ranging from 4.5% to over 10%, and triggering long-term inflationary pressures due to rising input costs and local labor wages. However, amidst this fragmentation, opportunities arise through the "China Plus One" (C+1) strategy, which encourages investment relocation to Southeast Asia. Indonesia has capitalized on this momentum through industrial downstreaming policies, particularly in nickel, and by strengthening economic sovereignty through Local Currency Transaction (LCT) initiatives to reduce dependence on specific global currencies. In conclusion, the transition toward a polarized world order requires Indonesia to implement principles of active neutrality and legal certainty to maintain its strategic position within the future restructuring of global value chains.